A Review-Reflection on African Feminisms 2019: Theorising from the Epicentres of Our Agency, Wits University, Johannesburg, South Africa. Issue 1 (10th May 2021) - Burger, Bibi; Khosi, Motlatsi; Brydon, Lavinia
Abstract : In this co-authored review-reflection, we discuss the African Feminisms 2019 conference, offering a snapshot of the vital and emboldening African feminist work being conducted by researchers, cultural producers and creative practitioners at all levels of their careers, as well as a sense of the emotional labour that this work entails. We note the particular, shocking event that took place in South Africa just prior to the conference informed the papers, performances and ensuing discussions. We also note that the conference and many of its attendees advocated for a variety of approaches (and more than one feminism) when seeking to challenge power.